Dog Man : Mothering heights / 10. - Pilkey, Dav, 1966- (Pilkey, Dav, 1966- Dog Man., 2021)
"Dog Man is down on his luck, Petey confronts his not so purr-fect past, and Grampa is up to no good. The world is spinning out of control as new villains spill into town. Everything seems dark and full of despair. But hope is not lost. Can the incredible power of love save the day?"--Provided by publisher.